TRATEGI BADAN USAHA MILIK DESA (BUMDES) BHUWANA SARI JAYA DALAM MENINGKATKAN PENDAPATAN ASLI DESA DI DESA PADANGSAMBIAN KAJA, KECAMATAN DENPASAR BARAT, KOTA DENPASAR - Agustini, Ni Komang Tri; Wirantari, I Dewa Ayu Putri; Yudartha, I Putu Dharmanu (CITIZEN CHARTER; Vol 2 No 2 (2022): Administrasi Publik 2022, 2023)
BUMDes Bhuwana Sari Jaya has a program in the field of trade, namely large trade and small trade, then a program in the field of services, namely waste management services and online counter payment services. Because the existence of BUMDes is still being helped recently and is still in the process of development, in its implementation still found some problems, namely (1) difficulty finding suppliers (2) lack of socialization and promotion ; (3) do not have a warehouse storage of goods ; (4) lack of cooperation with related parties This study uses qualitative descriptive approach and data collection techniques used are observation, interview, and documentation .The data analysis technique used is SWOT analysis. The results of this study are that researchers provide alternative strategies to BUMDes Bhuwana Sari Jaya in an effort to increase the village's original income Keywords: Strategy, Village Owned Enterprises (BUMDes) , Village Original Income (PADes)